1994
DOI: 10.1037/0033-2909.116.3.429
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in personality: A meta-analysis.

Abstract: Four meta-analyses were conducted to examine gender differences in personality in the literature (1958-1992) and in normative data for well-known personality inventories (1940-1992). Males were found to be more assertive and had slightly higher self-esteem than females. Females were higher than males in extraversion, anxiety, trust, and, especially, tender-mindedness (e.g., nurturance). There were no noteworthy sex differences in social anxiety, impulsiveness, activity, ideas (e.g., reflectiveness), locus of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

169
1,195
20
61

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,881 publications
(1,445 citation statements)
references
References 185 publications
169
1,195
20
61
Order By: Relevance
“…Agreeableness findings are also consistent with well-replicated results from earlier life phases (Costa et al, 2001;Feingold, 1994). Both evolutionary and social role theory explanations have been proffered for the consistent finding that women tend to be more nurturing.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Agreeableness findings are also consistent with well-replicated results from earlier life phases (Costa et al, 2001;Feingold, 1994). Both evolutionary and social role theory explanations have been proffered for the consistent finding that women tend to be more nurturing.…”
Section: Discussionsupporting
confidence: 78%
“…Earlier work on trait gender differences used almost exclusively young adults (cf. Feingold, 1994), and findings of observer-rated trait gender differences both in the U.S. and other cultures used college-age targets for these ratings .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This disparity may have had some influence on the outcome. A large metaanalysis, however, has indicated that there is little difference in impulsivity between males and females, with a median effect size of 0.03 (Feingold, 1994). Consistent with previous studies of temporal discounting, it was necessary to disregard some data due to inappropriate responding.…”
Section: Discussionmentioning
confidence: 70%
“…Primary psychopathy is regarded as being linked to an underactive BIS system, which is characterized by regulating behavior such as anxiety, higher levels of which are usually found for women than men (e.g., Feingold, 1994;Kessler et al, 1994;Lewinsohn, Gotlib, Lewinsohn, Seeley, & Allen, 1998). …”
Section: Discussionmentioning
confidence: 99%